Application of the TDABC model in the logistics process using different capacity cost rates - Paulo Afonso; Alex Santana (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: The understanding of logistics process in terms of costs and profitability is a complex task and there is a need of more research and applied work on these issues. In this research project, the concepts underlying Time-Driven Activity Based Costing (TDABC) have been used in the context of logistics costs. Design/methodology/approach: A Distribution Centre of wood and carpentry related materials has been studied. A multidisciplinary team has been composed to support the project including the researchers and three employees of the company responsible for accounting, logistics and warehousing. The design and implementation of the costing model asked for a deep understanding of the different tasks and processes that should be considered. Accordingly, a TDABC model for the logistics function was developed. Findings: The cost model presented here is supported on a series of time equations designed for the logistics function which allow the analysis and discussion of costs and profitability of different cost objects namely, products, clients, distribution channels, processes and activities. The cost of unused capacity and the effectiveness of logistics processes are also highlighted in this model. Research limitations/implications: In a case study, results and implications cannot be directly or immediately generalized. Nevertheless, the proposed time equations and cost model can be easily adapted to explain other types of logistics functions and it gives the foundations or other TDABC models with more than one capacity cost rate. Practical implications: The TDABC model developed in this case study can be used in similar cases and as a basis for the analysis of logistics costs in other logistics processes. Furthermore, managers can rely on the proposed approach to analyze products' profitability and logistics cost structure. Originality/value: In this case, different capacity cost rates were computed in order to reflect appropriately the logistics function which was presented in two different processes: internal logistics and distribution. These processes have specific resources allocated and should be measured differently. This is in line with Kaplan and Anderson (2004, 2007) who have suggested a more complex TDABC model with more than one capacity cost rate for these situations.
Keywords: 650; logistics costs; Time-Driven Activity Based Costing (TDABC); capacity costs; capacity cost rate; case study